9+9+2(x-2)=5x+8-2x

Simple and best practice solution for 9+9+2(x-2)=5x+8-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+9+2(x-2)=5x+8-2x equation:


Simplifying
9 + 9 + 2(x + -2) = 5x + 8 + -2x

Reorder the terms:
9 + 9 + 2(-2 + x) = 5x + 8 + -2x
9 + 9 + (-2 * 2 + x * 2) = 5x + 8 + -2x
9 + 9 + (-4 + 2x) = 5x + 8 + -2x

Combine like terms: 9 + 9 = 18
18 + -4 + 2x = 5x + 8 + -2x

Combine like terms: 18 + -4 = 14
14 + 2x = 5x + 8 + -2x

Reorder the terms:
14 + 2x = 8 + 5x + -2x

Combine like terms: 5x + -2x = 3x
14 + 2x = 8 + 3x

Solving
14 + 2x = 8 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
14 + 2x + -3x = 8 + 3x + -3x

Combine like terms: 2x + -3x = -1x
14 + -1x = 8 + 3x + -3x

Combine like terms: 3x + -3x = 0
14 + -1x = 8 + 0
14 + -1x = 8

Add '-14' to each side of the equation.
14 + -14 + -1x = 8 + -14

Combine like terms: 14 + -14 = 0
0 + -1x = 8 + -14
-1x = 8 + -14

Combine like terms: 8 + -14 = -6
-1x = -6

Divide each side by '-1'.
x = 6

Simplifying
x = 6

See similar equations:

| 12x+3=26 | | -8=2/3 | | 3x+9+6x=81 | | 5xn=2500 | | -10x+y+3=4y-13 | | (7p^2+4q)+-8p^2= | | 3x+7+2x+3=90 | | 7.88+4=62.09444+2x | | 12y=-15 | | .25(x+y)=15-x | | 1.8x+4569=0 | | 7(6-2(-37))=5(3(-37)+1) | | 35=4(b-4) | | 6x+3+9x=3(x+2) | | 7d-3c=f+d | | 2i+14=28 | | -6(1x+9)=-78 | | 2y+8-5y=-1 | | 4(-4-3x)=-40 | | 6(t-4)+8t=7(2t+3)-13 | | 2(-5+3x)=44 | | -2x-18=-4x-6 | | 9q+q-20=100 | | -6(-5x+1)=-6 | | 7y+9=39 | | -9k(7k+7)= | | 6(8+7x)=510 | | 4y-8y=16 | | -3(1x-1)=-15 | | -6d(4+5d)= | | 4x-(-3x)+10=17 | | 9x-9y=-63 |

Equations solver categories